The ADDIE Model in Instructional Design: NUST MISIS Case Study - M. V. Lukanina; S. G. Merkulova (Высшее образование в России, 2023)
Theoretical and methodological analysis of research devoted to pedagogical design has revealed a shortage of empirical design model implementation descriptions. The article examines the case of ADDIE model application to design an «English Language» course for master degree students at University of Science and Technology MISIS. New approaches to course design are vital to raise education competitiveness, which in turn is subject to objective contemporary social trends. The first stage of ADDIE model (Analysis) was based on needs assessment conducted among master degree students in the form of questionnaires, as well as 2020-2023 course curricula analysis in terms of competencies indicated by major courses departments for the subject area “English Language” in accordance with the FSES HE 3++ requirements. The article gives insight into course description, structure and principles which reflect the coherent progress of Design, Development and Implementation stages. Evaluation process is demonstrated through post-course questionnaire analysis to assess the dynamics of student satisfaction, as well as the analysis of course examination/completion results in 2020-2021 approbation year, after conceptual and content changes were made. The data show that the program fully complies with the expectations of master degree students of non-linguistics majors from the «English Language» course, allows to ensure positive foreign language acquisition and enhanced course completion. The conclusion drawn is that the application of five-stage-ADDIE framework makes for smooth and clear course design, given 1 semester and mixed-level master degree students of different non-linguistics majors.